2022
DOI: 10.1039/d2ta00133k
|View full text |Cite
|
Sign up to set email alerts
|

High-corrosion-resistance mechanism of graphitized platelet-type carbon nanofibers in the OER in a concentrated alkaline electrolyte

Abstract: Carbon materials are used as electrocatalyst supports and conductive additives in various electrodes for electrochemical energy conversion and storage because of their high electrical conductivity and chemical stability. However, they...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…2) show the sidewalls of the TiNi-CNFs comprise mostly of basal graphene planes, whereas in case of CrNi-CNFs, the edge planes of graphene sheets point outwards. Edge planes are considered to be more reactive than basal planes [34][35][36]. Thus, we can reasonably assume that CrNi-CNFs will form specific attachments with a few functional groups that are energetically most favorable.…”
Section: Resultsmentioning
confidence: 99%
“…2) show the sidewalls of the TiNi-CNFs comprise mostly of basal graphene planes, whereas in case of CrNi-CNFs, the edge planes of graphene sheets point outwards. Edge planes are considered to be more reactive than basal planes [34][35][36]. Thus, we can reasonably assume that CrNi-CNFs will form specific attachments with a few functional groups that are energetically most favorable.…”
Section: Resultsmentioning
confidence: 99%
“…Han and co-worker 48 reported that selective introduction of C-O-C functional groups on the edge of graphitic carbon can effectively improve the stability of the material in terms of electro-oxidation corrosion in acidic systems. On the other hand, Sato 49 et al found that pCNFs surfaces passivated with hydroxyl groups exhibited high resistance to carbon corrosion at high anodic potentials in concentrated alkaline electrolytes. Therefore, the C-O species produced on the surface of carbon papers during electro-oxidation corrosion can inhibit the carbon papers from being further corroded.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the deterioration of the carbon support has been identified as a major factor contributing to instability in catalyst systems. This degradation can result in catalyst detachment from the support and interface degradation. Various characterization techniques, including electrochemical mass spectrometry ,, and Raman spectroscopy, , have provided evidence supporting these observations. These findings highlight the significance of addressing the stability of the carbon support to ensure the enduring durability and performance of catalyst systems.…”
Section: Introductionmentioning
confidence: 88%